Incentives in Basic Research - Lazear, Edward P. (Journal of Labor Economics, 1997)
Individuals involved in basic research, like other workers, respond to incentives. Funding agencies provide implicit incentives when they specify the rules by which awards are made. The following analysis is an exercise in understanding incentives at an applied level. Specific rules are examined. What is the effect of rewarding past effort? What happens when a few large awards are replaced by many small awards? How does the timing of an award affect effort? How does an agency choose which topics to fund? Socially optimal rules are derived.